The role of Theory of Mind and Empathy levels in Anxiety Disorders Symptomatology - G. Santarelli; M. Innocenti; V. Faggi; V. Miglietta; I. Colpizzi; F. Galassi; G. Castellini; V. Ricca (European Psychiatry, 2022)
Introduction